SHARIAH LAW AND ISLAMIC FINANCE AS TOOLS FOR ECONOMIC EMPOWERMENT IN RURAL INDONESIA - Amila Yanti; Seo Jiwon; Lee Jiwon (Yayasan Adra Karima Hubbi, 2025)
Shariah law and Islamic finance have emerged as powerful tools for promoting economic empowerment, particularly in rural areas where poverty and financial exclusion are prevalent. In Indonesia, the world’s largest Muslim-majority country, Islamic finance offers unique opportunities to address economic disparities and foster inclusive growth. This study examines the role of Shariah law and Islamic finance in empowering rural communities in Indonesia, focusing on their impact on poverty alleviation, financial inclusion, and sustainable development. The research aims to identify the challenges and opportunities associated with implementing Islamic finance in rural areas and propose strategies for enhancing its effectiveness. Using a mixed-methods approach, this study combines quantitative analysis of socio-economic data with qualitative interviews with rural communities, Islamic financial institutions, and policymakers. Data were analyzed to assess the impact of Islamic finance on income levels, access to financial services, and community development. The findings reveal that Islamic finance, particularly through instruments such as zakat, waqf, and microfinance, has a positive impact on economic empowerment in rural areas. However, challenges such as lack of awareness, limited infrastructure, and regulatory gaps hinder its full potential. The study concludes that enhancing the role of Shariah law and Islamic finance in rural Indonesia requires targeted strategies, including education, infrastructure development, and regulatory reforms.